Increasing the effectiveness of messages promoting responsible undergraduate drinking: tailoring to personality and matching to context - Pilling, Valerie Kay (Kansas State University, 2008)
Two studies address the serious problem of college student binge drinking. Both studies identify factors that improve the effectiveness of public service announcements (PSAs) encouraging responsible drinking presented through a website simulation. Study 1 tested four levels of Message Personalization (i.e., extent to which the PSA targets important aspects of the individual's personality) by comparing the effectiveness of messages matched to the person's Big Five personality traits, their actual self-schema, their ideal self-schema, or a non-personalized control message. Matching to actual self-schema has been found to be effective in past research. However, it was expected that the more thoroughly personalized the message, the more effective it would be. Results revealed that in no instance was the most thoroughly personalized condition (Big Five matched) or the alternate way of matching to schema (ideal self-schema) more effective than the actual self-schema matching. When designing PSAs, there appears to be a threshold of personalization. Research related to testing PSAs discouraging binge drinking should continue to pursue self-schema matching rather than the more complicated Big Five matching. Study 2 tested Person Matching (i.e., whether the PSA matches the person's self-schema type or not) and two types of Context Matching (i.e., whether the PSA matches the Topic or Values of the message context) to determine their relative influence on the effectiveness of the PSA. It was expected that PSAs matched to any of these factors would be more effective than messages not matched, and that Person Matching would be more influential on the PSAs effectiveness than the two types of context matching. Person Matching reduced intentions to drink while staying in/home, but Topic Matching reduced intentions to drink when going out, suggesting that different factors are important for PSAs targeting drinking behavior in different locations. The interaction of Topic Matching and Values Matching indicate that the PSA should not match the message context too closely. Again, there appears to be a matching threshold; increasing the number of factors the message matches does not increase message effectiveness, possibly because it makes the message too redundant with the webpage content.
Keywords: Binge drinking; Message tailoring; Health persuasion; Personality; Self-schema; Message context; Psychology, Social (0451)